(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Football in his mind of the goalkeeper in success tactical skills big important have The goalkeeper collective tactics within skills protection and in attack own on the contrary finds This skills in defense the team members with good communication do to them support show , returned the balls management , directly and indirectly in blows the wall organize to attack while the ball safe way to the game to put and fast the attack organize reach such as of cases consists of The goalkeeper play during collective to tactics compliance to do his himself and team for success the key will be Therefore , the goalkeeper in training sessions another aspects with one in line collective tactics training is also a place take need This of research the goal of the goalkeeper protection and on the attack collective tactics according to actions is learning